Clinical characteristics and outcomes of patients with chondroblastoma undergoing surgery with various adjuvant procedures: a retrospective study of 59 cases - Toru Hirozane; Tetsuya Sekita; Eisuke Kobayashi; Tomoaki Mori; Naofumi Asano; Toru Udaka; Takashi Tajima; Rumi Nakagawa; Kazutaka Kikuta; Akira Yoshiyama; Hideo Morioka; Itsuo Watanabe; et al. (BMC Surgery)
Abstract Background Chondroblastoma is classified as a benign bone tumor. However, postoperative local recurrence remains a concern. We analyzed the factors contributing to chondroblastoma local recurrence and the clinical challenges associated with treating these patients. Methods This retrospective study examined 59 patients followed up at our hospitals for ≥ 1 year after surgery during 1990–2020. The most common lesion site was the epiphyses of long bones (42 cases, 71%), including the femur, tibia, and humerus. Curettage was performed in 57 cases; 2 cases with an iliac lesion underwent resection. The median postoperative follow-up period was 47 months. Clinical features of chondroblastoma were retrospectively investigated, and local recurrence and postoperative functional outcomes were assessed. Results Local recurrence occurred in 9% (5/57) of patients after curettage but not in the resected cases. The median time to local recurrence was 14 months. The local recurrence-free survival (LRFS) rate for all patients was 92.7% at 2 years and 88.3% at 5 years. All patients with local recurrence were aged < 17 years at the time of surgery. Local recurrence was observed in the proximal humerus in two cases and the calcaneus, acetabulum, and distal femur in one case each. None of the adjuvant procedures (high-speed burr, ablation, bone replacement materials, and preoperative denosumab) helped reduce local recurrence risk (P > 0.05). Trends toward fewer local recurrences were observed in the group treated using the high-speed burr and in the group not treated using bone replacement materials. Among the groups treated with bone replacement materials, artificial bone achieved the best LRFS rate, followed by allograft and autograft. At the final follow-up, the mean Musculoskeletal Tumor Society score was 29.8 (range: 25–30), indicating excellent postoperative functional outcomes. Joint degeneration was observed in five patients. Patients with local recurrence had a high degree of disability and joint deformity (P < 0.05). Two patients received preoperative denosumab and neither experienced local recurrence nor functional impairments. Conclusions Good oncological and functional outcomes were achieved. Age < 17 years was associated with a high risk of local recurrence after curettage (P = 0.0198). Patients with local recurrence exhibited poorer functional outcomes. High-speed burr may help reduce the recurrence risk. If bone grafts are necessary, materials with low biocompatibility, including artificial bone, may be optimal. Managing patients with chondroblastoma should encompass curative and functional aspects.